Appetite influences the responses to meal ingestion. Issue 8 (31st March 2017) - Pribic, T.; Nieto, A.; Hernandez, L.; Malagelada, C.; Accarino, A.; Azpiroz, F.
Abstract: Background: We have previously shown that the postprandial experience includes cognitive sensations, such as satiety and fullness, with a hedonic dimension involving digestive well‐being and mood. Preload conditioning has been shown to modulate appetite and food consumption under certain conditions, but its effects on the responses to meal ingestion are not clear. We hypothesized that appetite modulation by preload conditioning has differential effects on the cognitive and the emotive responses to meal ingestion. Methods: The effects of preload conditioning (ingestion of a low‐ vs a high‐calorie breakfast) on appetite and on the cognitive and emotive responses to a comfort probe meal ingested 2 hours later (ham and cheese sandwich with orange juice; 300 mL, 425 Kcal) was tested in healthy subjects (n=12) in a cross‐over design. Sensations were measured at regular intervals 15 minutes before and 60 minutes after the probe meal. Key Results: As compared to the low‐calorie breakfast, the high‐calorie breakfast reduced basal hunger sensation and influenced the responses to the subsequent probe meal: it increased satiety (4.3±0.2 score vs 2.7±0.2 score; P <.001) and fullness (5.4±0.5 score vs 3.1±0.5; P <.001), but reduced the expected postprandial experience of digestive well‐being after a palatable meal (1.3±0.7 score vs 3.0±0.3; P =.045). Conclusion and Inferences: Appetite modulation by preload conditioning has differential effects on the cognitive and emotive responses to a meal. Preload conditioning of the postprandial experience may be applicable to dietary planning and prevention of postprandial symptoms. Abstract : Effect of appetite on the responses to a meal. As compared to a low‐calorie breakfast, a high‐calorie breakfast reduced basal hunger sensation, and selectively influenced the responses to a meal ingested 2 hour later: it increased satiety and fullness, but reduced the expected postprandial experience of digestive well‐being.